2018
DOI: 10.3389/fimmu.2018.01680
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Specific Deletion of Peptidylarginine Deiminase 4 Mitigates Atherosclerosis

Abstract: Increasing evidence suggests that neutrophil extracellular traps (NETs) may play a role in promoting atherosclerotic plaque lesions in humans and in murine models. The exact pathways involved in NET-driven atherogenesis remain to be systematically characterized. To assess the extent to which myeloid-specific peptidylarginine deiminase 4 (PAD4) and PAD4-dependent NET formation contribute to atherosclerosis, mice with myeloid-specific deletion of PAD4 were generated and backcrossed to Apoe−/− mice. The kinetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 46 publications
(71 reference statements)
4
69
3
Order By: Relevance
“…Padi4 -/-NETs decreased vasculopathic and immunostimulatory effects. We and others have demonstrated that NETs can induce and amplify pathogenic type I IFN responses and promote vascular damage in SLE and atherosclerosis models (20,33,42,43). Given the putative role of PADs in NET formation (13), we sought to determine whether the differences observed in disease progression among the different mouse groups were due to differential effects on the ability of neutrophils to form NETs in the presence or absence of PADs.…”
Section: Resultsmentioning
confidence: 99%
“…Padi4 -/-NETs decreased vasculopathic and immunostimulatory effects. We and others have demonstrated that NETs can induce and amplify pathogenic type I IFN responses and promote vascular damage in SLE and atherosclerosis models (20,33,42,43). Given the putative role of PADs in NET formation (13), we sought to determine whether the differences observed in disease progression among the different mouse groups were due to differential effects on the ability of neutrophils to form NETs in the presence or absence of PADs.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the role of peptidylarginine deiminase 4 (PAD4), an enzyme that catalyzes citrullination of histones, has been intensively studied in association with NET formation. Several reports have argued that PAD4 activity is essential for NET formation 14,[35][36][37][38][39][40][41] , and contrary others disputed that PAD4 is not crucial for NET formation or the antimicrobial defense mechanism in vivo [42][43][44][45] . Specifically, NET formation in Klebsiella pneumonia-induced pneumonia was investigated showing NET-like structures surrounding Klebsiella bacteria at sites of immune infiltration in both Pad4 −/− and Pad4 +/+ mice.…”
Section: Nets and Eets In Bacterial Infectionsmentioning
confidence: 99%
“…Previous studies have shown that accumulation of extracellular DNA, particularly NETotic, necrotic, and necroptotic DNA is involved in atherosclerotic plaque progression [6][7][8] . Most importantly, treatment with DNase1 has been demonstrated to prevent plaque progression in early atherosclerosis 9,19 and promote plaque regression in diabetic mice 20 . Based on these previous studies as well as our data demonstrating impaired DNase response during hypercholesterolemia (Figure 2E), we next addressed the specific question whether restoration of DNase activity via exogenous supplementation of DNase1 could decrease plaque inflammation and prevent plaque progression specifically in the context of advanced atherosclerosis which has not been explored so far.…”
Section: Dnase1 Treatment Decreases Atherosclerotic Plaque Extracellumentioning
confidence: 99%
“…To this end, we fed Apoe -/mice a high fat-high cholesterol western-type diet (WD) for 16 weeks which leads to generation of advanced atherosclerotic plaques characterized by large necrotic areas. Post 16 weeks of WD feeding, the mice were randomized into two groups with one group of mice receiving DNase1 (400 U, intravenously) 19 three times a week for 4 weeks, while the other group was administered an equal volume of 1X-PBS as control. At the end of 4 weeks of treatment, both groups of mice had similar body weight and metabolic parameters including blood glucose, total cholesterol, and triglycerides ( Supplementary Figure 2A-D).…”
Section: Dnase1 Treatment Decreases Atherosclerotic Plaque Extracellumentioning
confidence: 99%
See 1 more Smart Citation